Trends in Salmonella enteric serovar Typhi in Nairobi, Kenya from 2004 to 2006 - Doris Mueni Mengo; Sam Kariuki; Ann Muigai; Gunturu Revathi (Journal of Infection in Developing Countries)
Background: Typhoid fever is a global health problem. The World Health Organization (WHO) estimates that the current annual global burden of typhoid is approximately 22 million new cases, 5% of which are fatal.